Quality Award Untuk Mengevaluasi Pencapaian Implementasi Manajemen Kualitas Perusahaan (Studi Kasus: Evaluasi Implementasi Six Sigma di Perusahaan X) - Damayanti, Retno Wulan (Performa: Media Ilmiah Teknik Industri, 2008)
Company can utilize Quality Award model to measure and evaluate efficacy of its quality managementimplementation. Three model which is often used is Deming Prize (DP), Malcolm Baldrige National Quality Award (MBNQA), and European Quality Award EQA). EQA is newest development model. Dutch Quality Award (DQA) is appreciation of quality in Dutch which its development follow EQA. Case Real how to measure quality management in company is given to describe way of utilizing Quality Award to measure and evaluate efficacy quality management implementation in company X .